Kajian Potensi Kayu Manis dan Teh sebagai Pangan Antidiabetes - Nawasari Indah Putri S. (Politeknik Kesehatan Tanjung Karang, 2018)
Diabetes mellitus is a metabolic disease characterized by hyperglycemia due to defects in insulin secretion, insulin action, or both. Type 2 Diabetes Mellitus (T2DM) can be controlled by healthy food and adequate physical activities. Some foods can be used for diabetes control such as cinnamon and tea. This paper determined to study cinnamon and tea researches as an antidiabetic food. All researches about cinnamon and tea as an antidiabetic were collected. It was found that cinnamon (Cinnamomum burmanii Blume) and tea (Camelia sinensis L) have many health potentials, such as antioxidants, antibacterial, antidiabetic. Cinnamon shows the ability to lower fasting blood glucose, HbA1c, and plasma lipids; altered postprandial glucose patterns, increased antioxidants and decreased plasma inflammatory markers. In the other hand, tea as the second most consumed drinks in the world could preventing or controlling diabetes with decrease digestive enzyme and intestinal GLUT activity, decrease gluconeogenesis gene expression, increase insulin sensitivity, and protect beta pancreatic. Tea can prevent the risk of T2DM disease if consumed as much as 3 cups per day. It was concluded that both foods can be used to control type 2 diabetes mellitus if consumed in an adequate amount.